Pengaruh Investasi dan Pengangguran Terhadap Pertumbuhan Ekonomi serta Kemiskinan di Provinsi Bali - Diah Paramita, A.A. Istri; Purbadharmaja, I.B. Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 10, Oktober 2015 (pp.1194-1327), 2015)
Poverty and Economic Growth is an important indicator for the success of development of a country. This study aimed to analyze the presence or absence of significant influence investment and unemployment economic growth, to analyze the presence or absence of significant influence investment, unemployment and economic growth on poverty and to analyze the impact of investment and unemployment to poverty through economic growth. This study uses a period of years from 1993-2013 and using secondary data. The data obtained were tested by using path analysis (Path Analysis). The study states that, lngsung investment variable positive and impact on economic growth and unemployment are variable significant negative effect on economic growth. While variable direct investment and economic growth and a significant negative impact on poverty and unemployment are directly variable positive and significant impact on poverty. Furthermore, to influence variable investment against poverty through economic growth and a significant negative effect. For variable unemployment to poverty through economic growth and a significant positive effect.
Keywords: Investment; Unemployment; Economic Growth; Poverty